Embedding photosynthetic biorefineries with circular economies: Exploring the waste recycling potential of Arthrospira sp. to produce high quality by-products. (November 2018) - Sachdeva, Neha; Mascolo, Cyril; Wattiez, Ruddy; Leroy, Baptiste
Graphical abstract: Highlights: Urea and Nitrite tested (vs nitrate) between 8.5 and 120 mM on Arthrospira sp. PCC 8005. Modified cultivation approach avoids inhibitory effects of urea. Evaluation performed under batch and continuous feeding. Modified biochemical and proteomic profile exhibited by urea fed cultures. Higher protein and pigment content quantified in urea fed cells. Abstract: This study was conducted with the aim of embedding circular economies (waste recycling) with photosynthetic biorefineries, for production of commercially viable by-products. Since nitrogen source constitute the major input costs for commercial Arthrospira sp. production, the use of nitrogen rich wastewater for Arthrospira sp. cultivation could significantly reduce their production costs. This study evaluated the effects of high concentrations (8.5–120 mM) of alternative nitrogen sources (urea, ammonium and nitrite) on the biochemical, pigment and proteomic profile of Arthrospira sp., under batch and continuous conditions. Arthrospira sp. cells fed with urea were quantified with modified biochemical and proteomic profile compared to the nitrate fed cells. No inhibitory effect of urea was observed on the biomass even at 120 mM. Nitrite fed cells exhibited comparable biochemical and proteomic profiles as nitrate fed cells. These results clearly indicated at the possibility of using urea rich wastewater streams for profitable cultivation of Arthrospira sp.